Study of Google Form-Based Assessment for Learning at UPT SD Negeri Binangun 01, Blitar Regency - Ciptaningsih (Jurnal Multidisiplin Madani, 2023)
Assessment for learning is an integral part of the learning process. One part of the assessment for learning is formative assessment. In the 21st century learning era, the implementation of formative assessments is often implemented on a digital basis. Google form is a platform that often used in the implementation of formative assessments. This study aims to examine the google form-based assessment for learning in class III to VI UPT SD Negeri Binangun 01 Blitar Regency. The research subjects consisted of 9 teachers and 173 students. The method used in this research is a qualitative descriptive research method. Research data obtained by data collection techniques from the results of questionnaires, observations, interviews, and documentation. Based on the analysis of the research data it was concluded that the use of google forms can make it easier for teachers to apply formative assessments in the form of objective questions, namely multiple choice, matching, true/false, and attitude scales (yess/no). The easeness experienced by the teacher can be seen in the activities making questions, making answer keys, determining scores, accessing answers and accessing student scores collectively on objective questions. Teachers encounter obstacles in making answer keys, determining scores, and accessing scores on questions in the form of short answers and essays. According to students, making formative assessments through google forms is more practical, attractive, safe, economical (paper and cost), in accordance with digital developments, and can be deleted easily. The weaknesses according to students and teachers are in the form of internet network constraints and electricity networks